Fabrication of surface-relief gratings on an azobenzene-containing epoxy-based polymer film using atomic force microscopy - Fernández, Raquel (2010)
Many studies have been reported on the photo-fabrication of surface-relief gratings (SRGs) in azo-polymer films using the interference of two laser beams of appropriate polarization. However, there are few reports in the literature concerning the electro-fabrication of SRGs on such types of polymer films. The goal of the work reported was the electro-patterning of an azobenzene-containing epoxy thermoplastic film. An epoxy-based polymer functionalized with an azo-chromophore was synthesized and characterized using thermal analysis. The reversible optical storage properties and photo-induced dichroism were studied. SRGs were fabricated on a film of the synthesized azobenzene-containing polymer using contact mode current-sensing atomic force microscopy which locally applied an electric field that aligned the azobenzene moieties. The anisotropic mass transport of the azo-polymer film was observed after applying an electric field. Additionally, the effect of the relief formation in the polymeric film surface was investigated by means of atomic force microscopy and electrostatic force microscopy. © 2010 Society of Chemical Industry.